PERANCANGAN INTERFACE E-INVENTORY BARANG BERBASIS WEB PADA UNIVERSITAS MUHAMMADIYAH JAMBI - Aryani, Reni; Marthiawati, Noneng (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2022)
Inventory is an activity to compile goods or record existing goods or materials correctly. Inventory of goods is also a recording of data related to goods or assets at Muhammadiyah Jambi University. Every item that is to be procured must be recorded properly as well as if the goods that have been procured and distributed must be recorded and reported properly and correctly as asset data. The purpose of this research is to help and facilitate employees in managing inventory of goods to be more effective and efficient, the method used is a prototyping system with the results of this research being the Design of the Goods E-Inventory Interface at Muhammadiyah Jambi University